Statistical Graphics in Czech Textbooks: A Comparative Content Analysis of Two Primary-Level Educational Areas - Marek, Tomáš; Maněnová, Martina (Revija za elementarno izobraževanje, 2024)
The study provides insight into the current state of cultivating statistical graphics skills in primary education in the Czech Republic through a quantitative content analysis of graphic data displays in textbooks and workbooks that are widely used in classrooms. The findings unveil noteworthy disparities in the frequency of statistical graphics among various textbooks, along with significant distinctions in the forms and types of statistical graphics employed across different educational areas.
Keywords: primary education, textbook analysis, content analysis, statistical graphics, charts.